El modelo de competencia económica practicable en el TLC entre Colombia y Estados Unidos (2005)
Nowadays, there is no more talking about free competition in the way as classical liberalism does, but there is about imperfect competition or monopoly competition in which each company man has the monopoly of its own products. Thus we face a mixt regime between free competition and monopoly. Is to forbid at the same time to allow certain behaviors. Free competition it is not necessary something good and monopoly is not necessary something wrong. What really matters is to preserve a price for the market, and for product sustituibility to exist, because it is relationship with demand elasticity, this is, with payment ability that comes form rent, even just a few competitors establishes the rigth parameter for a practice and answerable competition.